PERILAKU KONSUMTIF OLEH MASYARAKAT KONSUMSI DALAM PERSPEKTIF TEORI JEAN BAUDRILLARD [STUDI KASUS: TIKTOK SHOP] - Naufal Rizki Fadhillah; Suryo Ediyono (Marketgram Journal, 2023)
Social media has transformed into a place for trading activities. Promotional activities can be carried out easily through social media. This convenience can also lead to patterns of high consumption to consumptive behavior. This study aims to provide a descriptive analysis of the development of consumptive behavior in the TikTok shop which is analyzed using the concept of consumption society from Jean Baudrillard. The method used is a descriptive qualitative approach with natural observation techniques. The research population is a live audience of a TikTok account with a saturated sample. The data was obtained from observations of netizen interactions with TikTok Shop sellers via TikTok Live. The results obtained are that the method of selling through live broadcasts provides a new attraction and the consumptive behavior of netizens can be seen from the large number of viral non-needs items being sold. From these results it is concluded that the concept of consumption society is relevant to today's life, people tend to buy products because of desire, rather than need.